Knowledge of Snake Bite Management among Farmers - Fazah Nur Alif Fathur Rahmah; Zhafira Puspitarini; Tiara Aprilia Riyanti; Enggal Hadi Kurniyawan; Dicky Endrian Kurniawan; Alfid Tri Afandi; Kholid Rosyidi Muhammad Nur; Leni Agustin (Health and Technology Journal (HTechJ), 2025)
Snakebite is a global emergency that can result in death, especially among farmers. Knowledge of snakebite management for farmers can improve first aid skills and abilities. This study aims to analyze the importance of snakebite management on farmer safety. The method used in this research is a literature study by finding articles in 3 databases: Google Scholar (3,000 articles), Pubmed (4 articles), and ScienceDirect (196 articles). After that, the journals were sorted again with more specific keywords and years that met the criteria (2019-2024). The search keywords use two languages: the English keywords use "Knowledge" AND "Snakebite" AND "Management" AND "Farmers," and the Indonesian keywords use "Pengetahuan" AND "Manajemen" AND "Gigitan Ular" AND "Petani," then reviewed by reading the abstracts until finally reviewed by reading the abstract until finally a total of 10 titles were obtained. Based on these 10 articles, this study found that snakebite management education has an important effect on farmer safety. Snakebite first aid education and training have effectively improved farmers' knowledge and skills in handling snakebite cases. Approaches such as self-instructional modules, training workshops, and lectures have proven effective. Lack of first aid skills in snakebite incidents among farmers can be fatal. Therefore, nurses and health workers should educate farmers to reduce adverse outcomes and promote safer farming practices.